The Belt and Road Initiative, political involvement, and China's OFDI - Haoyuan Ding; Yi Li; Liang Wang; Chang Xue (International Studies of Economics)
Abstract The Belt and Road Initiative (BRI) is an important strategy for China. This study examines the effect of political involvement on firms' outward foreign direct investment (OFDI) in belt‐road countries after the BRI. Using merged Chinese nonfinancial listed firm data, the fDi Markets database, and the Thomson One database (formerly known as SDC Platinum) for the period 2008–2018, we find that political involvement has positive effect on firms' OFDI in belt‐road countries after the BRI. Furthermore, we find that the positive effect is heterogeneous across state‐owned enterprises (SOEs) and non‐SOEs. Political involvement has a positive effect on M&A for SOEs and Greenfield investment for non‐SOEs in belt‐road countries after the BRI. Our findings suggest that political involvement promotes firms' OFDI in belt‐road countries after the BRI and is helpful to the macro‐policy implementation.